Advances in ergonomics of manufacturing : managing the enterprise of the future : proceedings of the AHFE 2016 International Conference on Human Aspects of Advanced Manufacturing, July 27-31, 2016, Walt Disney World®, Florida, USA /: managing the enterprise of the future : proceedings of the AHFE 2016 International Conference on Human Aspects of Advanced Manufacturing, July 27-31, 2016, Walt Disney World®, Florida, USA. (2016) - Unknown
No abstract available